The impact of maternal protein restriction during rat pregnancy upon renal expression of angiotensin receptors and vasopressin-related aquaporins - Cornock Ruth; Langley-Evans Simon C; Mobasheri Ali; McMullen Sarah (BMC, 2010)
Abstract Background Maternal protein restriction during rat pregnancy is known to impact upon fetal development, growth and risk of disease in later life. It is of interest to understand how protein undernutrition influences the normal maternal adaptation to pregnancy. Here we investigated the mechanisms regulating renal haemodynamics and plasma volume during pregnancy, in the context of both normal and reduced plasma volume expansion. The study focused on expression of renal angiotensin receptors (ATR) and vasopressin-related aquaporins (AQP), hypothesising that an alteration in the balance of these proteins would be associated with pregnancy per se and with compromised plasma volume expansion in rats fed a low-protein diet. Methods Female Wistar rats were mated and fed a control (18% casein) or low-protein (9% casein) diet during pregnancy. Animals were anaesthetised on days 5, 10, 15 and 20 of gestation (n = 8/group/time-point) for determination of plasma volume using Evans Blue dye, prior to euthanasia and collection of tissues. Expression of the ATR subtypes and AQP2, 3 and 4 were assessed in maternal kidneys by PCR and western blotting. 24 non-pregnant Wistar rats underwent the same procedure at defined points of the oestrous cycle. Results As expected, pregnancy was associated with an increase in blood volume and haemodilution impacted upon red blood cell counts and haemoglobin concentrations. Expression of angiotensin II receptors and aquaporins 2, 3 and 4 was stable across all stages of the oestrus cycle. Interesting patterns of intra-renal protein expression were observed in response to pregnancy, including a significant down-regulation of AQP2. In contrast to previous literature and despite an apparent delay in blood volume expansion in low-protein fed rats, blood volume did not differ significantly between groups of pregnant animals. However, a significant down-regulation of AT2R protein expression was observed in low-protein fed animals alongside a decrease in creatinine clearance. Conclusion Regulatory systems involved in the pregnancy-induced plasma volume expansion are susceptible to the effects of maternal protein restriction.